SALUTE TO THE CORPS: 1,024 undergraduate volunteer police corps end training in style with the passing - out parade - Tan, Beng (New Straits Times, 2011)
IN a ceremony steeped in Royal Malaysian Police tradition 1,024 undergraduate volunteer police corps otherwise known as Suksis ended their training in a passing out parade at Universiti Teknologi Malaysia (UTM) recently.